Cyclovirobuxine D Ameliorates Experimental Diabetic Cardiomyopathy by Inhibiting Cardiomyocyte Pyroptosis via NLRP3 in vivo and in vitro - Gao, Ge; Fu, Lingyun; Xu, Yini; Tao, Ling; Guo, Ting; Fang, Guanqin; Zhang, Guangqiong; Wang, Shengquan; Qin, Ti; Luo, Peng; Shen, Xiangchun (Frontiers in Pharmacology, 2022)
Diabetic cardiomyopathy (DCM) is one of the common complications of diabetic patients, which can induce myocardial hypertrophy, cardiac fibrosis, and heart failure. Growing evidence has shown that the occurrence and development of DCM are accompanied by pyroptosis which is an NLRP3-mediated intense inflammatory cell death. Cyclovirobuxine D (CVB-D) has been shown to significantly ameliorate DCM and anti-inflammatory effects associated with cardiomyopathy, but it is unclear whether it has an effect on cardiomyocyte pyroptosis accompanying DCM. Therefore, the purpose of the present study was to explore the ameliorating effect of CVB-D on cardiomyocyte pyroptosis associated with DCM and its molecular regulation mechanism. Type 2 diabetes in C57BL/6 mice was reproduced by the high-fat and high-glucose diet (HFD) combined with low-dose streptozotocin (STZ). The characteristics of DCM were evaluated by cardiac ultrasonography, serum detection, and histopathological staining. The results suggested that CVB-D could significantly alleviate the cardiac pathology of DCM. Then, we explored the mechanism of CVB-D on primary neonatal rat cardiomyocyte (PNRCM) injury with high glucose (HG) in vitro to simulate the physiological environment of DCM. Preincubation with CVB-D could significantly increase cell viability, attenuate cytopathological changes and inhibit the expression levels of pyroptosis-related proteins. Further research found that the myocardial improvement effect of CVB-D was related to its inhibition of NLRP3 expression. In conclusion, our data suggest that CVB-D can ameliorate DCM by inhibiting cardiomyocyte pyroptosis via NLRP3, providing a novel molecular target for CVB-D clinical application.